2007
DOI: 10.1007/s00468-006-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of an African savanna tree, Bauhinia thonningii Schumacher, to defoliation, fire and climate

Abstract: This study investigated the growth responses to defoliation, fire-exposure and climate factors of a widespread Africana savanna tree, Bauhinia thonningii Schumacher, at a site in central Zambia. Experimental trees (n = 47) were either exposed to fire (n = 12) in the first half of the dry season or protected from fire (n = 35). Some of the fire-protected trees (n = 12) were subjected to artificial defoliation in two consecutive years. Phenological responses (bud break, leaf flush and leaf production) to fire-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…However, large seeds produced higher germination than other seed size categories. The present findings are in agreement with those reported by [8][9][10]. Esen et al [11] reported that large and heavy seeds contain larger amounts of reserves to stimulate germination, seedling survival, and growth.…”
Section: Discussionsupporting
confidence: 94%
“…However, large seeds produced higher germination than other seed size categories. The present findings are in agreement with those reported by [8][9][10]. Esen et al [11] reported that large and heavy seeds contain larger amounts of reserves to stimulate germination, seedling survival, and growth.…”
Section: Discussionsupporting
confidence: 94%
“…Multistemmed trees can be prevalent in areas experiencing fire as a result of a coppicing effect after disturbance (Chidumayo ; Werner & Franklin ). The dry savanna region responded to fires by an increase in the proportion of multistemmed individuals, whilst in the wet savanna a similar response was observed only where burns were annual.…”
Section: Discussionmentioning
confidence: 99%
“…These saplings, otherwise known as ‘Gulliver trees’, are stuck in the fire zone for years and are unable to reproduce fully, thus limiting tree recruitment into the canopy (Werner ). Additionally, trees experiencing disturbance are often prone to producing multiple stems, akin to the effects of coppicing (Chidumayo ; Werner & Franklin ). Therefore, savannas experiencing fire may have a higher prevalence of multistemmed trees, which may affect habitat structure for fauna communities, especially bird populations (Sirami et al .…”
Section: Introductionmentioning
confidence: 99%
“…extensive crown vine coverage remains extensive from year to year); (ii) such variables influence the development and growth of the tree, limiting its future growth; and (iii) inherent genetic and site differences such as soil fertility and water availability among trees are immutable or strongly persistent. While the phenomenon of growth autocorrelation has been widely reported (Swaine et al 1987a;Kohyama & Hara 1989;Kammesheidt et al 2003;Chidumayo 2007;Drobyshev et al 2007), its strength, persistence, and importance relative to other explanatory variables is just beginning to be investigated. Growth autocorrelation's dramatic impact on population models (e.g.…”
Section: Introductionmentioning
confidence: 99%